Dual Use of Electronic Cigarettes and Cigarettes Elevates Risk of Chronic Obstructive Pulmonary Disease and Mental Health Issues: Insights from a Korean Health Survey - Kim CY; Park SH; Seong Y; Choi YJ; Park HJ; Cho JH; Byun MK (International Journal of COPD)
Chi Young Kim,1 Sang Ho Park,2 Yeseul Seong,3 Yong Jun Choi,1 Hye Jung Park,1 Jae Hwa Cho,1 Min Kwang Byun1 1Department of Internal Medicine, Yonsei University College of Medicine, Seoul, Republic of Korea; 2Department of Clinical Research Design and Evaluation, Samsung Advanced Institute for Health Sciences and Technology, Sungkyunkwan University, Seoul, Republic of Korea; 3Department of Internal Medicine, Gangnam Severance Hospital, Yonsei University College of Medicine, Seoul, Republic of KoreaCorrespondence: Min Kwang Byun, Department of Internal Medicine, Yonsei University College of Medicine, Eonjuro Gangnam-Gu, Seoul, 06229, Republic of Korea, Email littmann@yuhs.acPurpose: Significant differences exist between the toxicity and adverse outcomes of conventional cigarettes and electronic cigarettes. However, spirometry-based clinical outcome analyses in the general population have not been widely studied. This study aimed to investigate the factors associated with electronic cigarette use among individuals with different smoking status and pulmonary function test results.Patients and Methods: This study was conducted in Korea using data from the Korean National Health and Nutrition Examination Survey from 2013 to 2019. Participants who reported baseline clinical information, including smoking status, and underwent a pulmonary function test, were included.Results: In total, 19,356 participants, including current smokers, former smokers, and participants who never smoked, participated in this study. Among the participants who smoked, 5.7% reported current electronic cigarette use, including dual users (who use conventional cigarettes and electronic cigarettes). Factors associated with e-cigarette use included male sex, younger age, higher education level, higher household income, and being current or former heavy smoker. Additionally, cigarette users had the highest prevalence of chronic obstructive pulmonary disease, followed by dual users and electronic cigarette-only users (P < 0.001). Furthermore, individuals with anxiety and depression were significantly more prevalent among dual users than among those who had never smoked (P < 0.001).Conclusion: This study indicates an association between e-cigarette use and individual factors, including sex, age, education level, and income level. Electronic cigarette use, including dual use, is associated with chronic obstructive pulmonary disease. Additionally, anxiety and depression were highest among dual users, followed by those among conventional cigarette users.Keywords: airflow obstruction, chronic obstructive pulmonary disease, depression, E-cigarette, anxiety